Pressure-induced structural phase transitions in the multiferroic four-layer Aurivillius ceramic Bi5FeTi3O15. Issue 11 (1st August 2020) - Ferreira, Wellington Castro; Rodrigues, Gelson Luiz Clemente; Araújo, Bruno Sousa; de Aguiar, Francisco André Andrade; de Abreu Silva, Ariel Nonato Almeida; Fechine, Pierre Basílio Almeida; de Araujo Paschoal, Carlos William; Ayala, Alejandro Pedro
Abstract: The structural stability of the multiferroic four-layer Aurivillius ceramic Bi5 FeTi3 O15 (BFTO) under hydrostatic pressure was investigated in situ by synchrotron X-ray powder diffraction (SXRPD) and Raman spectroscopy. Measurements performed up to 15 GPa allowed the identification of two well-defined structural phase transitions. The orthorhombic phase (at ambient conditions) transforms into a tetragonal one around 3.2 GPa and a new orthorhombic phase rises around 7.5 GPa. Both phase transitions are evidenced by the pressure dependence of the lattice parameters and vibrational mode frequencies. The analysis of the induced strain indicates that the transitions are of second-order and first-order, respectively. Subtle changes in the Raman spectra and powder patterns suggest the onset of a new phase around 10.5 GPa.